Cutting Edge Geometry Effect on Plastic Deformation of Titanium Alloy - Korovin G. I.; Filippov A. V. Andrey Vladimirovich; Proskokov A. V. Andrey Vladimirovich; Gorbatenko V. V. Victoria Valerievna (2016, 2016)
Title screen